Optimalisasi Perawatan Pesawat Terbang dengan CPM, PERT, dan Linear Programming pada Perusahaan MRO - Riani Nurdin; Uyuunul Mauidzoh; Nurfi Ahmadi (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2026)
Maintenance, Repair, and Overhaul (MRO) companies face significant challenges in completing aircraft maintenance projects on time and within budget. The existing gap lies in the optimization of planning methods integration to minimize project duration and cost. This study aims to assess the balance between time and cost in aircraft maintenance projects by showing the benefits of combining CPM, PERT, and Linear Programming. Data were obtained from the A02-CHECK activity at a national MRO company. CPM and PERT were used to find the critical path and estimate project duration, while LP was used to optimize time and cost on that path. The project duration decreased from 6,199 to 4,547 minutes, with the critical path in activities A-C-E-G-H and an 84.13% success probability. Using LP, the duration dropped further to 4,090 minutes at a total cost of $202. It can be concluded that the integration of these three methods is effective in accelerating projects without exceeding the budget. The main contribution of this research is the development of an integrated approach to aircraft maintenance project planning which can capable of reducing the risk of delays and budget overruns. in addition, it also provides practical solutions for MRO companies